Clinical Outcomes of Allograft Superior Capsular Reconstruction for Irreparable Posterosuperior Rotator Cuff Tears in Patients Aged 65 and Older: A Retrospective Study - Hsin-Pei Sung; Wei-Cheng Chen; Yung-Chang Lu; Tsung-Yu Lin; Po-Ju Wu (Formosan Journal of Musculoskeletal Disorders)
Background: Superior capsular reconstruction (SCR) has emerged as the favored surgical intervention for younger, more active individuals afflicted with irreparable rotator cuff tears. For older patients lacking shoulder osteoarthritis and deemed unsuitable candidates for arthroplasty, SCR serves as a viable joint-preserving therapeutic approach. Nonetheless, there exists a deficiency in clinical data concerning the outcomes of SCR conducted within an older demographic. Objectives: The objective of this study was to assess functional outcomes, pain relief, and allograft survival rates in patients aged 65 years and older undergoing SCR. Materials and Methods: The study spanned from January 2019 to February 2022. Data were collected from patients aged 65 years and older who had undergone arthroscopic dermal allograft SCR for massive irreparable rotator cuff tears, with a clinical follow-up of at least 2 years postoperatively. Each patient underwent postoperative assessment, including routine radiographic analysis for acromiohumeral distances, ultrasound imaging at 1 and 3 months post-SCR, and magnetic resonance imaging (MRI) at least 6 months post-SCR. The outcome measures comprised forward flexion, the Visual Analog Scale (VAS), American Shoulder and Elbow Surgeons, Constant, and Single Assessment Numeric Evaluation scores. Results: A total of 51 patients were included in the study, with a mean age of 72.4 years (range: 65–88), comprising 29 females and 22 males. Results indicated a significant postoperative improvement in VAS score (5.1–1.6, P < 0.001) and functional outcomes. Postoperative MRI demonstrated intact grafts in 46 patients, constituting a survival rate of 90.2%. Conversely, graft failure was observed in 5 male patients. Conclusions: SCR emerges as a favorable intervention for achieving pain relief, enhancing functional capacity, and facilitating a high rate of allograft healing among patients aged 65 years and older. Additionally, females within this age group demonstrate a notable advantage with a higher graft survival rate.